Surface modification of carbon-based adsorbents derived from coal gasification slag for the efficient adsorption of trimethoprim - Zhiqiang Yang; Jia Liu; Qingchao Li (PLoS ONE, 2026)
Given that pristine water bodies are irreplaceable for maintaining ecosystem homeostasis, the remediation of antibiotic-contaminated aquatic systems has emerged as a pivotal challenge. This research used flotation residual carbon (FRC) obtained from coal gasification coarse slag (CGCS) as a precursor and adopted the H 2 O 2 liquid-phase oxidation method to prepare a low-cost and efficient adsorbent by optimizing process parameters such as modification temperature, time, and oxidant concentration. The H 2 O 2 treated flotation residual carbon was denoted as HFRC. Batch adsorption assays revealed that, under their respective optimal conditions, equilibrium uptakes of Trimethoprim (TMP) by FRC and HFRC reached 54.02 mg/g and 80.01 mg/g, with equilibrium times of 270 min and 360 min. Comprehensive characterization, molecular simulations, and model fitting collectively elucidated the adsorption mechanism and the kinetic intensification of TMP. H 2 O 2 modification markedly increased the abundance of oxygen-containing functionalities. On this basis, the van der Waals and electrostatic interactions between HFRC and TMP were significantly enhanced, accompanied by a pronounced increase in hydrogen-bond density, which collectively accelerated the TMP adsorption kinetics. HFRC also exhibited exceptional dynamic adsorption performance in the fixed-bed column. Overall, HFRC integrates rapid removal performance with resource-cycling benefits and superior environmental adaptability, offering an economically and ecologically synergistic paradigm for the valorization of CGCS and the remediation of antibiotic-impaired waters.